Формирование трудового потенциала человеческих ресурсов в условиях рынка. (Путеводитель предпринимателя)
The essence of the concept «labour potential of human resources» is analysed in the article. Its marking technique is resulted. The basic congenital and gotten properties of the person's character are shown, that influent to formation of labour potential in aggregate. The special attention is given to the analysis of these properties and their account by company management in a practice of human resources management.